Pengaruh social media marketing activities terhadap loyalitas pelanggan pada produk lokal UMKM di aplikasi Shopee - Nur Sayyidah Salsabila; Indrawati Indrawati (Jurnal Inspirasi Bisnis dan Manajemen, 2022)
Abstract. The main purpose of this research is to examine the influence of social media marketing activities on customer loyalty through customer equity drivers with three dimensions: value equity, brand equity, relationship equity in local MSMEs products in the Shopee application. Non-probability sampling was utilized, along with purposive sampling. This survey included 275 respondents who used Shopee application users in Indonesia and had purchased local products. In this study, descriptive analysis and SmartPLS 3.0 software was used for SEM analysis. According to the results of this investigation, perceived social media marketing activities have a positive significant influence on value equity, brand equity, and relationship equity. Value equity, brand equity, and relationship equity have a positive significant effect on customer loyalty. Value equity, brand equity, and relationship equity will mediate the relationship between perceived social media marketing activities and customer loyalty. Keywords: Brand Equity; Customer Loyalty; Relationship Equity; Social Media Marketing Activities; Value Equity. Abstrak. Tujuan utama dari penelitian ini adalah untuk mengkaji pengaruh social media marketing activities pada loyalitas pelanggan melalui customer equity drivers’ dengan tiga dimensi: value equity, brand equity, and relationship equity pada produk UMKM lokal di aplikasi Shopee. Non-probability sampling digunakan, bersama dengan purposive sampling. Survei ini melibatkan 275 responden pengguna aplikasi Shopee di Indonesia dan pernah membeli produk lokal. Dalam penelitian ini, analisis deskriptif dan software SmartPLS 3.0 digunakan untuk analisis SEM. Menurut hasil dari investigasi ini, perceived social media marketing activities berpegaruh positif signifikan terhadap value equity, brand equity, dan relationship equity. Value equity, brand equity, dan relationship equity berpengaruh positif signifikan terhadap loyalitas pelanggan. Value equity, brand equity, dan relationship equity akan memediasi hubungan antara perceived social media marketing activities dan loyalitas pelanggan.   Kata Kunci: Brand Equity; Loyalitas Pelanggan; Relationship Equity; Social Media Marketing Activities; Value Equity.